Microglial activation evaluated using flutriciclamide (11F‐GE180) in subjects with cognitive impairment: Neuroimaging / Optimal neuroimaging measures for tracking disease progression. (7th December 2020) - Calsolaro, Valeria; Hinz, Rainer; Femminella, Grazia Daniela; Pasqualetti, Giuseppe; Buckley, Chris J; Gentleman, Steve; Brooks, David J; Edison, Paul
Abstract: Background: Microglial activation plays a significant role, and could be quantified using PET tracers targeting TSPO. We evaluated the use of Flutriciclamide PET tracer in a cohort of subject diagnosed with Alzheimer's Disease (AD) or Mild Cognitive Impairment (MCI), using spectral analysis Method: Twenty‐three subjects with AD, fourteen with MCI and eleven healthy controls (HC) underwent 3T MRI and Flutriciclamide PET with arterial input. Spectral analysis was used to create parametric maps, and IRF at 90 minutes was sampled for region of interest analysis. IRF90 parametric maps were also used for voxel‐wise SPM group analysis. Result: Mean ages were 70.65±6.2‐ for AD, 70.3±6‐ for MCI and 63.4±1.4‐ for HCs. MCI and AD were age‐matched. Significant difference was found in the MMSE scores between AD and MCI (mean and SD respectively 21.8±3.7‐ and 26.8±3‐, p<0.001) and between AD and HC (mean and SD of HC 28.9±1.4‐, p<0.001). Significant difference was found in the hippocampal volumes between AD and MCI (mean 2711±477 on the left and 2750±455 on the right for AD, and 3942±284 and 4048±394 for MCI, p<0.01) and between AD and HC (mean 3942±284 on the left and 4048±394 on the right for HC, p<0.001).Significant difference was also found between MCI and HC (p=0.01 for left hippocampus, p=0.02 for the right one). When evaluating the IRF90 flutriciclamide uptake, significantly higher uptake was found in the AD group compared to HC in temporal (p<0.01), parietal (p=0.012), occipital (p=0.03) lobes and composite brain (p=0.01). In the AD group, IRF90 was higher in temporal lobe when compared with MCI group (p=0.04). SPM group wise analysis showed significantly higher uptake in part of temporal, parietal and occipital regions in AD compared to HCs, and a smaller cluster including part of temporal and occipital lobes when comparing AD and MCI. Conclusion: Our study, conducted in a population with a clinical diagnosis of AD or MCI demonstrated higher widespread flutriciclamide uptake in the AD group compared with HC, and more limited difference between AD and MCI, and can be used quantify neuroinflammation.